THE ROLE OF PRIMARY CLASS TEXTBOOKS IN YOUTH EDUCATION IN THE PROCESS OF MODERN EDUCATION (Conferencea, 2023)
This article talks about the role of elementary school textbooks in the education of young people in the modern education process. Based on scientific data, the author analyzed the problem on the basis of existing literature and studied the specific aspects of the role of elementary school textbooks in the education of young people in the modern education process.